STANDARDIZING THE INFORMATION MODEL OF COMPETENCE AND RELATED OBJECTS - Maxim V. Sutyagin (Открытое образование (Москва))
The article considers questions of harmonization of requirements of professional standards and federal educational standards, the international standardization of information models of competences, an electronic portfolio, protection of personal information, development of the national standards harmonizing requirements of the Russian legislation and the international standards.